Comparison of magnesium alloys and poly‐l‐lactide screws as degradable implants in a canine fracture model. Issue 7 (22nd June 2015) - Marukawa, Eriko; Tamai, Masato; Takahashi, Yukinobu; Hatakeyama, Ichiro; Sato, Masaru; Higuchi, Yusuke; Kakidachi, Hiroshi; Taniguchi, Hirofumi; Sakamoto, Takamitsu; Honda, Jun; Omura, Ken; Harada, Hiroyuki
Abstract: The aims of this study were to evaluate in vivo the biological responses to implants composed of biodegradable anodized WE43 (containing magnesium yttrium, rare earth elements and zirconium; Elektron SynerMag®) magnesium alloy, monolithic WE43 magnesium alloy and poly‐l ‐lactic acid (PLLA), which are commonly used materials in clinic settings, and to evaluate the effectiveness of the materials as bone screws. The effectiveness of the magnesium alloy implants in osteosynthesis was evaluated using a bone fracture model involving the tibia of beagle dogs. For the monolithic WE43 implants, radiological, and histological evaluation revealed that bone trabeculae around the implanted monolithic WE43 decreased because of an inflammatory response. However, there was no damage due to hydrogen gas or inflammatory response in the bone tissue around the anodized WE43 implants. After 4 weeks, all the PLLA implants ( n  = 3) had broken but the WE43 implants had not ( n  = 6). These results suggest that the WE43 implants had sufficient strength to fix bone fractures at load‐bearing sites in orthopedic and oral maxillofacial surgery. Therefore, these biodegradable magnesium alloys are good candidates for replacing biodegradable polymers. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1282–1289, 2016.